2017
DOI: 10.1002/cbdv.201700276
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Pimarane‐Type Diterpenes from Marine Organisms

Abstract: Marine organisms represent an abundant sources of bioactive natural products with unique chemical structure. Pimarane diterpenes are a structurally diverse family of natural products with various biological activities and pharmacological properties. A prolific source of new marine-derived pimarane diterpenes have attracted considerable interest because of their unique structural diversity and varied biological activities, including antimicrobial, antitumor, and antiproliferative activities. This review provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In particular, a lot of work has been done with chiral carbinols due to their ubiquitous presence in natural products. 25 The CD comparison of 3-oxo-oryzalexin C, (11), with that of authentic 3-oxo (+) sandaracopimaradiene (ent-configuration) and 3-oxo (−) sandaracopimaradiene showed that oryzalexin C, 11 (cisoid enone with characteristic Cotton effects at +335 nm, +250 nm, and negative 210 nm), is identical in AC with that of the positive enantiomer and antipodal with that of the negative one. 84 This latter is based on the use of (R)-and (S)-α-methoxy-αtrifluoromethyl phenylacetic acid chlorides to convert the secondary alcohols to the corresponding diastereomeric esters followed by the comparison of their 1 H-NMR data.…”
Section: Stereochemical Assigment Of Pimarane Diterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a lot of work has been done with chiral carbinols due to their ubiquitous presence in natural products. 25 The CD comparison of 3-oxo-oryzalexin C, (11), with that of authentic 3-oxo (+) sandaracopimaradiene (ent-configuration) and 3-oxo (−) sandaracopimaradiene showed that oryzalexin C, 11 (cisoid enone with characteristic Cotton effects at +335 nm, +250 nm, and negative 210 nm), is identical in AC with that of the positive enantiomer and antipodal with that of the negative one. 84 This latter is based on the use of (R)-and (S)-α-methoxy-αtrifluoromethyl phenylacetic acid chlorides to convert the secondary alcohols to the corresponding diastereomeric esters followed by the comparison of their 1 H-NMR data.…”
Section: Stereochemical Assigment Of Pimarane Diterpenesmentioning
confidence: 99%
“…2 Pimarane diterpenes are frequently produced by plant and fungi but more rarely from bacteria, insects, and marine organisms 3,4 with interesting biological activities along with potential applications in agriculture 5,6 and medicine. 11 10 This review discusses the isolation from different natural sources as plants, fungi, and marine organisms; structure and relative or absolute configuration (AC) assignment; and finally, biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…1 This class of diterpenes can be derived from the original core by substitution, hydroxylation, acetylation, rearrangement, bromination, and ring expansion reactions. 2 Since the isolation of pimaric acid, the rst example of this class, in 1839, 3 pimarane diterpenoids have attracted considerable interest due to their remarkable structural diversity and great antimalarial, 4 antibacterial, 5 antifungal, 6 antiviral, 7,8 phytotoxic, 6 cytotoxic, [9][10][11][12] AChE-inhibitory, 13 and anti-inammatory activities. 14 Sarcosomataceous fungi (Ascomycota), usually known as degraders of wood or as pathogens, 15 have been reported to produce spirobisnaphthalenes, 16,17 lactones, 15,[18][19][20][21] naphthalones, 21 cyclohexenones, 22 and isocoumarins.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Carbocyclic diterpenes, also known as diterpenoids, represent a large class of natural compounds found in plants, algae, lichens, marine invertebrates, bacteria and are produced by various fungi and fungal endophytes. [7][8][9][10][11][12][13][14][15] The highly oxygenated diterpenoid (HOD) that belong to a small group of diterpenoid peroxides are of great interest to researchers, since representatives of this group demonstrate a wide range of biological activities. [3,8,[16][17][18][19][20][21][22][23][24][25] The chemical structure of the molecule and its biological activity are in a certain relationship which is called SAR (Structure-Activity Relationship).…”
Section: Introductionmentioning
confidence: 99%